POLICEAI: UPAYA AKSELERASI PENANGGULANGAN KETIDAKPROFESIONALAN APARAT KEPOLISIAN TERHADAP PELAYANAN MASYARAKAT - Hamriani, Indarwati; Tussaida, Fauzia (Jurnal Legislatif, 2024)
Based on data from Komnas HAM, a significant number of public complaints are directed at police officers, particularly concerning unprofessionalism and procedural inaccuracies by law enforcement officials. The data indicates that public concerns about the performance and quality of police officers increase every year. Therefore, the purpose of this research is to identify the factors contributing to the unprofessionalism of police officers and to explore strategies and solutions to address these issues. The research method used is empirical research. The results reveal various factors that cause police officers to be perceived as unprofessional in carrying out their duties and responsibilities, including political intervention, where law enforcement is influenced by political interests; structural weaknesses exacerbated by the era of technological advancements, leading to the emergence of new types of crimes that require police officers to adopt an adaptive approach; and investigative challenges, particularly difficulties in gathering strong evidence. Consequently, the introduction of PoliceAI, which is equipped with various features, is expected to assist police officers in overcoming these challenges and enhancing law enforcement in Indonesia. In conclusion, PoliceAI presents a practical and implementable solution to the challenges faced by police officers in law enforcement.